STUDI FENOMENOLOGI PENGALAMAN MAHASISWA PGSD DALAM MEMPELAJARI BAHASA INGGRIS SEBAGAI BAHASA ASING DI UNIVERSITAS NANI BILI NUSANTARA SORONG - Doni Sudibyo; Eliaser Ulimpa; Sriayu (LPPM Politeknik Saint Paul Sorong, 2026)
This study aims to explore the experiences of students in the Elementary School Teacher Education Program (PGSD) in learning English as a Foreign Language (EFL) at Universitas Nani Bili Nusantara Sorong. The study employed a qualitative approach with a phenomenological method to understand the students’ subjective experiences. The participants consisted of five PGSD students selected through purposive sampling. Data were collected through in-depth interviews and documentation. The data analysis used a phenomenological approach involving data reduction, categorization, and the interpretation of the essential meanings of participants’ experiences. The findings revealed that students’ experiences in learning English were influenced by three main aspects: (1) psychological factors such as self-confidence and anxiety, (2) academic factors such as limited vocabulary and difficulties in understanding grammar, and (3) learning environment factors, including the use of digital technology. In addition, students developed various learning strategies, such as independent learning through digital media and informal communication practices. These findings indicate that English learning for PGSD students’ needs to be designed in a more communicative, contextual, and technology-based manner to improve learning effectiveness.